Dynamic absolute distance measurement with nanometer-precision and MHz acquisition rate using a frequency comb-based combined method. (March 2023) - Ahn, Changmin; Na, Yongjin; Kim, Jungwon
Highlights: A new dynamic distance measurement method is demonstrated by combining electro-optic sampling with microwave phase detection. 300-mm non-ambiguity range and 49-nm precision are made possible even at very short (1-μs) acquisition time. The best precision of 0.99-nm is achieved at 0.22-s, corresponding to unprecedented 169 dB dynamic range. Abstract: Distance metrology is crucial in supporting modern science and technology such as satellites interconnection, autonomous driving, motion control, and precision manufacturing. A combined method, which is a simultaneous distance measurement with multiple methods, was developed and widely utilized to increase the measurable range while maintaining high precision. However, the measurement speed has been limited to a few kHz due to the requirement for combining a precision measurement with a long-range measurement. In this work, we present a new dynamic distance measurement method based on electro-optic sampling timing detection (EOS-TD) that can preserve the non-ambiguity range (NAR) extension even at >1 MHz acquisition rate. By combining the EOS-TD-based pulse time-of-flight detection method with a microwave phase detection method, 300-mm NAR and 49-nm precision are made possible at 1-μs acquisition time. With longer averaging time, the best precision of 0.99 nm is achieved at 0.22-s acquisition time, corresponding to 169 dB maximum dynamic range. As a demonstration experiment, two mirrors that were ∼83 mm apart and each controlled by a piezo actuator with hundreds of nanometers of displacement variations had their distance between them precisely measured.